Addressing the food supply chain challenges for UK disadvantaged communities - Sawyerr, Emmanuel; Bourlakis, Michael (The Chartered Institute of Logistics and Transport, 2023)
Introduction: In pursuit of the United Nations (UN) Sustainable Development Goals (SDGs), many developed countries have invested various resources to address hunger as specified under the UN SDG2: Zero Hunger. Even in the West, there is a growing population of disadvantaged persons (such as single-parent households, low-income families, lone and vulnerable adults, the physically and mentally disabled, among others) who disproportionately suffer from diet-related ill-health, food insecurity and food poverty. The UK is no different. Despite various practical and research interventions, the role of logistics and supply chain management in addressing these challenges in the UK has been underexplored. Consequently, this research investigates the supply chains that deliver food to the disadvantaged to identify the processes, infrastructure and challenges, and to highlight ongoing attempts and propositions for addressing these. The paper starts with a literature review of food waste and surplus food redistribution and food supply chain mapping in the UK. This is followed by a discussion of the data collection and analysis approaches for mapping the food supply chain serving disadvantaged consumers. The findings and discussions section presents an overview of the processes and infrastructure in the supply chain and presents recommendations for the various actors and stakeholders for process optimisation. The paper concludes with the research and practical implications.